2021
DOI: 10.3390/ijerph18105145
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Support, Emotional Intelligence and Family Function in Adolescence

Abstract: Background: During adolescence, although the peer group exerts a strong influence on how the individual thinks and feels and on personal social values, the family still exerts a sustaining and supporting role. This study analyzed the relationships established between family function, emotional intelligence and perceived interpersonal support in adolescence. Method: The sample was made up of 1287 high school students aged 14 to 18 (M = 15.11; SD = 0.91) in the province of Almeria (Spain). Results: The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 58 publications
4
12
0
Order By: Relevance
“…The analyses carried out show that the relationship between prosocial behaviours of empathy, respect and social relations and the school climate is moderated by family functioning. This statement is associated with other studies indicating that family functioning affects adolescents' behaviour both outside and inside the school environment [20][21][22][23]. However, this moderation in leadership is not found, which may be related to the fact that this dimension of prosocial behaviours depends more on factors such as interactions among the class group than on family functionality [25].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The analyses carried out show that the relationship between prosocial behaviours of empathy, respect and social relations and the school climate is moderated by family functioning. This statement is associated with other studies indicating that family functioning affects adolescents' behaviour both outside and inside the school environment [20][21][22][23]. However, this moderation in leadership is not found, which may be related to the fact that this dimension of prosocial behaviours depends more on factors such as interactions among the class group than on family functionality [25].…”
Section: Discussionsupporting
confidence: 75%
“…Family functioning is one of the most relevant factors that serve to assess the quality of the family environment, communication, coping and conflict resolution, emotional response, established roles and behavioural control among family members [19]. The benefits of positive family functioning in adolescence are reflected in current studies, which indicate that students with highly functioning families are reported to have greater social support than young people with dysfunctional families [20]. Furthermore, satisfaction with family life is estimated to be a mediator of the relationship between social connectedness and problematic social network use [21].…”
Section: Introductionmentioning
confidence: 79%
“…Thus, the family function may be a protective factor for the prognosis of IBD patients, influencing their mental and physical health. In addition, the family function can bring about continuous optimization of prognosis, improve the sense of happiness, and attain a long-term s‘ quality of life ( 13 , 14 ), which supports the notion that family function can bring about continuous optimization of prognosis. Research shows that family function might impact a patient's mental health.…”
Section: Introductionsupporting
confidence: 63%
“…Men in particular need to develop emotional skills and he gives many examples of high intelligence that didn't work out because they had problems with their skills. He found from his research that people with emotional intelligence generally have successful relationships with family, friends and co-workers (Barragán Martín et al, 2021). They are also successful because they are persistent in the face of setbacks and channel their emotional energy toward achieving their goals.…”
Section: Discussionmentioning
confidence: 99%